(untitled) (International Journal of Built Environment and Sustainability, 2023)
The student housing market has had free and unsystematic development in developing cities with a high density of universities. In Ho Chi Minh City, the situation has resulted in specific negative urban issues and low life quality for students. This study aimed to clarify how students allocate around a university, the residential zones’ characteristics, and preferences for the residential zones. We analyzed survey data of 304 students at a university in Ho Chi Minh City. We addressed the differences among residential zones through statistical analyses of group differences. A multinomial logit model was deployed to explore students’ choice of residential zones. Results show significant characteristics that affected the students’ choice, including academic levels, motorcycle usage, employment status, family income, household member, household size, and gender. Some implications for policymaking in the student housing market were raised regarding residential zones, integrating transport systems, travel behavior, and employment opportunities. The study enhanced knowledge of the student housing situation (i.e., residential zones or residential allocation) and the student’s preferences. Policymakers and practitioners developing student housing markets, built environments, and related services can benefit from this study. The findings apply to the specific city under investigation and are useful to other Southeast Asian cities with similar socio-cultural contexts.